A opinião pública na produção literária e acadêmica de relações públicas no Brasil : 1960-2019 - Becker, Gustavo Eugênio Hasse (2019)
This research aimed to map the literary and academic production of public relations in Brazil, as well as to understand the approaches on the subject of public opinion in that production. A consultation with five university libraries, the Fundação Biblioteca Nacional, and eight stricto sensu graduate programs took place to collect data in books and theses that contained in their title or subtitle the phrase public relations and, in their content, address public opinion. Supported by methodological procedures characteristic of discursive textual analysis (MORAES, 2002), the research found twenty books and six theses that addressed public opinion, contemplating the established purpose. The study allowed the identification of text fragments with public opinion approach that were distributed among seven emerging research categories, namely: contextualized public opinion; public opinion as an instance of command, decision making and judgment; public opinion resulting from the action of the media and other artifacts; public opinion resulting from a psychosocial process; public opinion resulting from a collective unanimous process; public opinion resulting from an international/world process; and public opinion and public relations action. The analysis of these findings, in the light of the theoretical choices based on Tarde (2005), Machiavelli (1977), Childs (1964) and Augras (1970), led to the emergence of the following understandings: a significant portion of the analyzed productions attributes to the media the power to form and influence public opinion and, in a direct relationship with this finding, confirms the perceptions that public opinion is currently an international/world process; in almost half of the books in which public opinion is mentioned, the repetition of concepts is observed; the theses are found in only one stricto sensu graduate program in the country, with productions that address public opinion; Brazilian author Cândido Teobaldo de Souza Andrade wrote the most about public opinion in the public relations area.